Association of Occupational Workload and Ergonomic Risk Factorswith Musculoskeletal Injuries among Endoscopy Practitioners in India: An Analytical Study (Bangladesh Journal of Medical Science, 2026)
Abstract not availableBangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S311-S324